Translation and censorship in different times and landscapes - Seruya, Teresa, 1950-; Moniz, Maria Lin, 1955- (Cambridge Scholars Pub., 2008)
This volume is a selection of papers presented at the international conference on Translation and Censorship. From the 18th Century to the Present Day, held in Lisbon in November 2006. Although censorship in Spain under Franco dictatorship has already be.